2016
DOI: 10.1186/s12870-016-0808-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of miRNAs and targets in flax (Linum usitatissimum) under saline, alkaline, and saline-alkaline stresses

Abstract: BackgroundMicroRNAs (miRNAs) play a critical role in responses to biotic and abiotic stress and have been characterized in a large number of plant species. Although flax (Linum usitatissimum L.) is one of the most important fiber and oil crops worldwide, no reports have been published describing flax miRNAs (Lus-miRNAs) induced in response to saline, alkaline, and saline-alkaline stresses.ResultsIn this work, combined small RNA and degradome deep sequencing was used to analyze flax libraries constructed after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 56 publications
2
34
0
4
Order By: Relevance
“…However, overexpression of WRKY45 in Arabidopsis increased phosphate uptake [35]. For flax, the involvement of WRKY family genes only in saline-alkaline stress response was known [36, 37]. In the present work, we revealed significant expression decrease of WRKY33 , WRKY40 , and WRKY70 under NPK compared to P conditions for flax genotypes without LIS-1 (‘Stormont cirrus’ without LIS-1 and ‘Bethune’).…”
Section: Discussionsupporting
confidence: 49%
“…However, overexpression of WRKY45 in Arabidopsis increased phosphate uptake [35]. For flax, the involvement of WRKY family genes only in saline-alkaline stress response was known [36, 37]. In the present work, we revealed significant expression decrease of WRKY33 , WRKY40 , and WRKY70 under NPK compared to P conditions for flax genotypes without LIS-1 (‘Stormont cirrus’ without LIS-1 and ‘Bethune’).…”
Section: Discussionsupporting
confidence: 49%
“…Compared to saline soils (NaCl/Na 2 SO 4 ), alkaline soils are composed primarily of NaHCO 3 /Na 2 CO 3 . An increasing number of researches have suggested that bicarbonate/carbonate alkaline stress imposes much severer repression on plant growth through the complex damages derived from excess Na + , HCO 3 − /CO 3 2− , high-pH (> 8.5) and poor soil structure [ 2 ]. Hence, improving the bicarbonate/carbonate alkaline tolerance is of profound importance to crop yields, and will greatly secure the food security.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the molecular mechanisms underlying the responses of flax to unfavorable environments are intensively studied. In this regard, changes in the expression of stress-responsive genes and microRNAs have been detected in flax plants under abiotic stresses, such as drought [ 8 ], salinity and alkalinity [ 9 , 10 ], nutrient imbalance [ 11 ], and high concentrations of aluminum ions [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%